1572-1587 (H.980-995) yılları arası Üsküdar Mahkemesi Kadı Sicilleri’nin sosyal ve iktisadi açıdan değerlendirmesi - Yalçın, Nihat (My University, 2009)
Şer’iyye sicilleri, muhteva ettikleri askeri, iktisadi, hukuki ve sosyal veriler açısından Osmanlı tarihinin ana kaynaklarındandır. Bu çalışmada Üsküdar şer’iyye sicillerinden 1572- 1587 (H. 980- 995) yılları kayıtlarını ihtiva eden 58-67 numaraları arasındaki 10 defter incelenmiştir. Bu defterlerde, konularına göre hükümler, idarecilerle kadı arasındaki muhtelif yazışmalar, ferman suretleri vb. de bulunmaktadır. Bu 10 defterden 60 numaralı defterin tamamı, 61 ve 66 numaralı defterlerin de büyük bir kısmı Arapça’dır. Buna rağmen bu defterlerdeki Arapça hükümlerin de çok büyük çoğunluğunun konuları ve tarihleri tespit edilmiştir. Toplam varak sayısı 952’dir ve 7000’in üzerinde kaydı muhtevîdir. Çalışmaya defterler okunarak başlanmış ve okunan her kayıt konu, tarih, defter numarası, varak ve hüküm numarasına göre tasnif edilmiştir. Önsözde kadı sicillerinin önemi hakkında, giriş bölümünde şer‘iyye sicilleri, kadılar ve yapılan çalışma hakkında bilgi verilmiştir.

Sher'iyye records are one of the main sources of Ottoman History. The data in Sher'iyye records are really valuable since they include information about military, economy, judicial system and society. In this study, ten books from Uskudar Sher'iyye records were examined. These are the books between 58 - 67. These books are written in the period between the years 1572- 1587 (H. 980- 995). These books includes some verdicts and correspondences etc. between administrators and the judge (Kaadı). One of the ten books scrutinized in this study, number 60, is totally in Arabic. Besides, the books 61 and 66 are mostly in Arabic. None of these books were excluded from the study and the judicial verdicts and decrees in Arabic were classified according to their subjects and dates. The number of total documents(varak) is 952, which comprise more than 7000 records. At the beginning of the study, the books were read. After being read, each record was classified according to subject, date, book number, document and verdict number. In the preface, some information is provided about the significance of judge (Kaadi) records. In the introduction, the reader finds some information regarding the Sher'iyye records, judges (Kaadis), and the study.
Keywords: Siciller; Tarih_Üsküdar; Yeniçağ Tarihi